Implementasi Perizinan Berusaha Berbasis Risiko Pada Usaha Wisata Bidang Penyediaan Akomodasi di Kabupaten Karangasem - I Wayan Mulyadi Pratama Sukerta; Ketut Kasta Arya Wijaya; Indah Permatasari (Jurnal Analogi Hukum, 2025)
A system of licensing is in place for enterprises in the lodging sector that is based on the degree of risk the firm poses. This system is known as accommodation risk-based business licensing. In this method, a number of potential risks to the company are evaluated before a permit is granted. These potential dangers may have nothing to do with safety, health, the environment, or anything else at all. Businesses providing lodging must adhere to all relevant rules and regulations and operate in a safe and responsible manner, which is why this permission is necessary. Law No. 10 of 2009 Concerning Tourism is the Law of the Republic of Indonesia Regulating Tourism. Many facets of the tourist industry, including lodging, are addressed by this statute. When it comes to developing tourism in a way that is both comprehensive and sustainable, this legislation governs the roles and responsibilities of the community, visitors, businesses, federal, and state governments. Consequently, this licensing aids in shielding the public and customers from any harm caused by the activities of housing businesses. Job Creation Law No. 6 of 2023 governs risk-based licensing, which includes lodging enterprises. A risk-based licensing system is put in place by the government under the Job Creation Law to streamline the licensing procedure for business actors.